Indigenous Onomastics in Zakes Mda’s The Heart of Redness: Anthroponymic and Toponymic Practices in a Postcolonial Context - Pule Seabi; Edward Montle; Mphoto Mogoboya (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
The continuous usage of colonial languages in Africa during and after colonisation creates an identity crisis in onomastics. African indigenous names have been polluted and replaced with colonial names due to the influence of colonial languages. Colonialism impacted the names of places and people in the African space, language played a major role, and black people started to adopt the colonial language and named themselves with this foriegn language. Thus, this paper analyses Zakes Mda`  s novel titled The Heart of Redness (2000) to investigate African identity-crisis through the onomastics of people (anthroponyms) and places (toponyms) of the indegenous (south) African people. The paper uses a qualitative research methodology to probe the colonial undertones within the names of people and places in the present day (South) Africa through prism of Mda`  s selected literary text.